UTILIZATION OF FERMENTED ORGANIC WASTES OF TOFU, RICE BRAN, AND CHICKEN MANURE TO INCREASE THE CULTURE PRODUCTION AND QUALITY OF SILK WORM (Tubifex sp) - Diana Chilmawati; Suminto .; Tristiana Yuniarti (LPPM Universitas Pekalongan, 2015)
The Effect of enrichment culture media through the combination of fermented tofu waste, rice bran, chicken manure to increase the production and quality of silk worm, Tubifex sp. was studied in this research. The experiment method was employed in this research by using complitely randomized design pattern with four treatments and three replicates, respectively. Those treatments were the combinations of 0% tofu waste, 0% rice bran, and 100% chicken manure (A), 35% tofu waste, 15% rice bran, and 50% chicken manure (B), 25% tofu waste, 25% rice bran, and 50% chicken manure (C), and 15% tofu waste, 35% rice bran, and 50% chicken manure as D treatment. The results shown that the enrichment culture media through the combination of tofu waste, rice bran, and chicken manure were siqnificantly effect (p<.05) on the total biomass production and protein content, but no siqnificantly effect on the total length growth of silk worm, Tubifex sp. However, the combination of 35% tofu waste, 15 rice bran, and 50% chicken manure was the best production and quality of silk worm, Tubifex sp.Key word : Tubifex sp., agriculture organic wastes, fermentation, quality, and culture production